Influence of exposure to light and storage period on color changes in gari produced from bio-fortified cassava (Manihot esculenta Crantz) varieties - Udemba IO; Olasanmi B; Iluebbey P (Global Journal of Ecology - Peertechz Publications, 2023)
Light degrades carotenoids and thus the color of bio-fortified gari during storage. This study was therefore conducted to evaluate the effect of exposure of bio-fortified gari to light during storage on its color. Gari samples obtained from the processing of fresh storage roots of three yellow root cassava varieties (TMSI011368, TMSI010593, and TMSI010539) and a white root variety (TMS30572) as check were packaged in three replicates in transparent white plastics containers (light condition) and blue plastics containers wrapped in black polythene bags (dark condition). These were stored on an open shelf in the laboratory in a 4 × 2 × 13 factorial experiment in a randomized complete block design. Immediately after processing and monthly for 12 months, the gari samples were evaluated for color using a scale of 1 (white) to 8 (pink). The result showed that yellowness of the gari from bio-fortified cassava varieties decreased over the storage period from 5.5 (TMS010539) immediately after processing to 2.5 (TMS010593, under both storage conditions) at 12 Months After Storage (MAS). The change was significantly (p < 0.05) influenced by variety, storage duration and storage condition. Gari from varieties TMSI011368 and TMSI010593 had the least (38.3%) and highest (50.2%) percentage reduction in yellowness, respectively at the end of the storage period (12 months). Across the storage period, the mean color of gari samples stored in the dark condition (3.37) was significantly higher than the mean color of gari samples exposed to light (3.22). Therefore, the proper selection of cassava variety and the use of packaging containers that screen light from bio-fortified gari during storage can best preserve its color and ensure the availability of a reasonable amount of carotenoids to consumers after long-term storage (12 months).